Challenges and Opportunities in Atrium Buildings: A Review - Bajracharya, Susan (Journal of the Institute of Engineering, 2014)
One of the most significant problems regarding the space conditioning of atriums is their relatively large volumes compared with traditional commercial and institutional spaces. This may lead to high energy consumption, if atriums are fully conditioned unless effective design strategies are implemented. Most people perceive atriums as indoor environments, not as outdoor or intermediate environments and therefore demand high comfort levels. It is often very difficult to achieve high thermal comfort and low energy consumption at same time. A 1 °C decrease in indoor temperature in winter will decrease energy consumption by 5 %. If people are aware of such relationships, it might lead them to accept atriums with lower temperatures in winter and higher temperature in summer and wear appropriate clothing while in atrium spaces, thus achieving considerable savings in energy use. DOI: http://dx.doi.org/10.3126/jie.v9i1.10671 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 65–68